PENDIDIKAN SEBAGAI PEMBENTUK KARAKTER BANGSA: ANALISIS KONSEP NEGARA IDEAL AL-FARABI - Intan Nur Aini; Dian Sri Utami; Hotimah; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
Education is one of the most important instruments in shaping national character and developing a civilized society. This study aims to analyze Al-Farabi's concept of the ideal state and examine the role of education in shaping national character based on his philosophical thought. This research employs a library research method by utilizing various sources, including books, scientific journals, academic articles, and Al-Farabi's works relevant to the topic. The collected data were analyzed using content analysis to identify the relationship between education, character formation, and the concept of the ideal state. The findings reveal that Al-Farabi viewed education as the primary means of developing knowledgeable, virtuous, and socially responsible individuals. In the concept of Al-Madinah Al-Fadhilah, education plays a strategic role in creating citizens who possess moral virtues and contribute to achieving collective happiness. Furthermore, Al-Farabi's ideas remain relevant in addressing contemporary moral challenges, particularly in strengthening character education in Indonesia. Therefore, value-based and moral-oriented education should continue to be developed as a foundation for building a harmonious, ethical, and prosperous society.